SPACE, TIME AND NATURE: THE PROCESS AND THE MYTH - Peluso, Marília Luiza; Pantoja, Wallace Wagner Rodrigues; Morales Arteaga, Pâmela Elizabeth; Araújo, Maxem Luiz de (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
The article fits into the debate regarding space, time and nature in dialogue with the world lived by subjects that build up themselves or are built as mythological heroes, source of speech and spacial concrete practices. It's a poorly explored field in Geography that recently approaches to the cultural dynamic debate, to the symbolic field and also to their spacialization processes.